2003
DOI: 10.1562/0031-8655(2003)077<0309:dpoafa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Autofluorescence for an Assisted Intraoperative Delineation of Glioblastoma Resection Margins¶

Abstract: The intrinsic autofluorescence properties of biological tissues can be affected by the occurrence of histological and biochemical alterations induced by pathological processes. In this study the potential of autofluorescence to distinguish tumor from normal tissues was investigated with the view of a real-time diagnostic application in neurosurgery to delineate glioblastoma resection margins. The autofluorescence properties of nonneoplastic and neoplastic tissues were analyzed on tissue sections and homogenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 33 publications
5
84
1
1
Order By: Relevance
“…Additionally, a broad and characteristic emission spectrum is induced, allowing the extraction of valuable spectral information. [46,47] Moreover, the use of a 405 nm light source also leads to the excitation of tissue autofluorescence, which could be used as an additional parameter for tissue discrimination [48][49][50] or serve as reference for the normalization of PpIX signals [27].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a broad and characteristic emission spectrum is induced, allowing the extraction of valuable spectral information. [46,47] Moreover, the use of a 405 nm light source also leads to the excitation of tissue autofluorescence, which could be used as an additional parameter for tissue discrimination [48][49][50] or serve as reference for the normalization of PpIX signals [27].…”
Section: Resultsmentioning
confidence: 99%
“…These include studies of glioblastoma [88][89][90][91][92][93], astrocytoma, oligodendroglioma, and metastatic carcinoma [90]. For example, combining fluorescence (excitation 337 nm) with diffuse reflectance spectroscopy at multiple excitation wavelengths [90] or using microspectrofluorometric measurements at a few excitation wavelengths [89], it has been shown that brain tumors can be distinguished from normal brain tissue with good sensitivity and specificity. Previously, the Marcu et al research group reported results on the time-resolved fluorescence of glioblastoma [92,93] and meningioma [94].…”
Section: Fluorescence Spectroscopy Of Brain Tumorsmentioning
confidence: 99%
“…Subsequently, Croce et al [89] used a similar method to analyze the autofluorescence properties of nonneoplastic and neoplastic tissues, those of homogenates by means of a microspectrofluorometer, and directly on patients affected by glioblastoma multiforme, during surgery, with a fiber optic probe. Fluorescence spectra of supernatants of both tumor and nonneoplastic tissue homogenates were excited using 366 and 405 nm.…”
Section: Steady-state Fluorescence Spectroscopymentioning
confidence: 99%
“…The samples were preserved at À808C until mounted for cryostatic sectioning (30-mm thickness). Tissue sections were submitted to measurements, according to a procedure already described, ensuring a reliable preservation of the autofluorescence properties of the in vivo condition [32].…”
Section: Ex Vivo Studymentioning
confidence: 99%